Incidence of Neonatal Sepsis in the Neonatal Intensive Care unit: A prospective study at Al Batool Teaching Hospital in Diyala Governorate - Qais Mahmood Almaroof, Sura; Mahmood Enad, Imad; Hussein Alwan, Shaima; Tariq Abdul Wahaab, Issam (Diyala Journal of Medicine, 2020)
Background:Sepsis is regarded as one of the most common causes of morbidity and mortality in neonates despite of recent advances in neonatal intensive care unit technologies. More than 40% of deaths among children below five years occur in the neonatal period and this accounts for about 3.1 million newborn deaths each year. Objective: To estimate the incidence of neonatal sepsis in the neonatal intensive care unit in Al-Batool teaching hospital in Diyala governorate. Patients and Methods: A sample of 1200 patients was prospectively collected over a period of 10 months extending from the 1st of Dec. 2018 till the 1st of Oct. 2019 in the neonatal intensive care unit at Al-Batool teaching hospital. All the admitted cases with clinical signs of sepsis at the time of admission or who developed sepsis during their hospital stay were assessed depending on the clinical and laboratory investigations. Results: This study revealed that the incidence of neonatal sepsis was 8.8%. There were significant relationships between development of neonatal sepsis and each of gestational age, state of amniotic membrane, mode of delivery and maternal fever (p-value = 0.0001 for each). In addition this study showed that there was insignificant relationship between the development of neonatal sepsis and gender of neonates, p-value equal to 0.463. Conclusion: The occurrence of neonatal sepsis depends on the presence of many factors that could be prenatal, perinatal and postnatal. In addition to that the infection control programs play an important role in controlling neonatal sepsis in the neonatal intensive care units. Therefore the incidence rate of neonatal sepsis reflect the quality of the provided health services in the health institutions and this might explain the relatively accepted rate of sepsis in our institution in relation to other studies as it was 8.8%.